BIOLOGICAL EVALUATION OF SAUSSUREA LAPPA ROOT EXTRACT FOR ANALGESIC AND ANTI- INFLAMMATORY ACTIVITY - Tejaswi, Juluri Krishna Dutta; Rajan, R. Govinda; Sara, P (Asian Journal of Pharmaceutical Research and Development, 2018)
The present study was designed to evaluate the Phytochemical Screening for Analgesic and Anti- inflammatory activities of Ethonolic extract of Saussurea lappa. The collected plant root material were washed, shade dried, and size reduced into small pieces. Dried materials were coarsely powdered and macerated with petroleum ether for 72 hrs. The plant material was extracted by using ethanol by the cold maceration method. The study concluded that the root extract have potential bioactive substances that may be used to formulate new drugs. The Flavo-Glycosides content in Ethonolic extract of Saussurea lappa root was extracted and results were compared with the standard for Analgesic and Anti- inflammatory activities. The results were compared with the standard using statistical method. However further investigation was required for structural elucidation and pharmacological properties. Keywords: Saussurea lappa, Ethonolic, Glycosides, Analgesic, Anti-inflammatory.